ANALISIS NORMATIF DAN YURIDIS TERHADAP IMPLEMENTASI UU NOMOR 23 TAHUN 2004 DALAM PENGANGANAN KEKERASAN DALAM RUMAH TANGGA DI INDONESIA - ROSYADI, FUAD; Zumrotun, Siti (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study aims to analyze the effectiveness of the implementation of Law No. 23/2004 on the Elimination of Domestic Violence (PKDRT Law), especially on the protection and fulfillment of victims' rights, as well as structural obstacles in its implementation. The approach used is normative juridical with a content analysis method of laws and regulations, secondary data from Komnas Perempuan, KPAI, LPSK, and case studies of court decisions. The main findings show that although the PKDRT Law is an important legal breakthrough, its implementation in the field is still weak, especially in the enforcement of Article 5 (types of violence), Article 26 (victims' rights), and Article 44 (punishment). The low sensitivity of the authorities, patriarchal culture, and the lack of witness and victim protection are the main obstacles. In conclusion, legal protection for victims of domestic violence in Indonesia still requires strengthening derivative regulations, improving the victim protection system, and increasing the understanding of officials and the public to realize substantive justice for victims.